Role of Design Thinking Approach to Technological Innovations in Organisational Performance: An Empirical Study of Indian Tech-Startups (Journal of Informatics Education and Research, 2025)
The present research work aims to understand, role of design thinking approach to revolutionize organizational performance, reshape business model by focusing on new ideas and customer-focused solutions in Indian tech-startups. This method has thereby; improved how they create products and plan strategies, helping them understand customer needs, think of creative ideas, and put useful innovations into action. Present study will also introduce, how design thinking approach is often; seen as a method for innovation and changing how organizations work, but it actually goes beyond that. Helps Indian tech-startups to make products which stand out, because it is a practical, user-friendly way of solving problems which can help create ideas, and provide these organizations with a competitive edge. Design thinking approach promotes a trial-and-error mindset to create solutions which are not only practical but, also valuable and beneficial for both users and the entire startup ecosystem. Usage of design thinking in such businesses and workflows brings great value, therefore; helping make sure the products created in Indian startups are attractive to users and realistic for the company’s resources and budget. 217 respondents associated with Indian tech-startups were surveyed to explore the factors that determines role and impact of design thinking approach to technological innovations in organisational performance. The study concludes that there is significant impact of design thinking approach to technological innovations on organisational performance.